2009
DOI: 10.2989/ajar.2009.8.1.2.715
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of mental health among Ugandan youth orphaned by AIDS

Abstract: The AIDS epidemic has disproportionately affected developing or low-income sub-Saharan African countries. Within the context of the epidemic, children and youth are at risk of losing their parents at an early age. The experience of orphanhood due to AIDS has the potential to negatively impact on a child's mental health. A qualitative study was conducted to comprehensively describe the experience of orphanhood and its impact on mental health from the culturally specific perspective of Ugandan youths. We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 0 publications
2
21
0
1
Order By: Relevance
“…These concepts emphasize that resilience applies to systems, involving families, communities, or broader social ecologies, and refers to the process of collective reflection, planning, and action to deal with encountered disturbances and challenges that may threaten or actually affect individual and communal well-being. The indicators generated by participants in this study show some overlap with other studies reporting culturally sensitive conceptualizations of resilience, wellbeing, or mental health (Ager, Akesson, et al, 2011;Harms, Kizza, Sebunnya, & Jack, 2009;Stark et al, 2009;Ungar & Liebenberg, 2011). For instance, sociability is consistently identified as an important indicator of youth well-being across different studies and contexts.…”
mentioning
confidence: 63%
“…These concepts emphasize that resilience applies to systems, involving families, communities, or broader social ecologies, and refers to the process of collective reflection, planning, and action to deal with encountered disturbances and challenges that may threaten or actually affect individual and communal well-being. The indicators generated by participants in this study show some overlap with other studies reporting culturally sensitive conceptualizations of resilience, wellbeing, or mental health (Ager, Akesson, et al, 2011;Harms, Kizza, Sebunnya, & Jack, 2009;Stark et al, 2009;Ungar & Liebenberg, 2011). For instance, sociability is consistently identified as an important indicator of youth well-being across different studies and contexts.…”
mentioning
confidence: 63%
“…Many studies (8/15) discussed participants’ experiences with reduced schooling during their parents’ illness or after their death (Ansell & Young, 2004; Chase, Wood, & Aggleton, 2006; Foster et al, 1997; Funkquist et al, 2007; Harms et al, 2009; Harms et al, 2010; Mangoma et al, 2008; Mmari, 2011; Oleke et al, 2006, 2007; van Blerk & Ansell, 2007; Young & Ansell, 2003). This was due to an inability to pay school fees or uniforms (Funkquist et al, 2007; Mangoma et al, 2008; Oleke et al, 2007; Young & Ansell, 2003) or being required to engage in paid work or chores (Chase et al, 2006; Foster et al, 1997; Mmari, 2011; Oleke et al, 2006, 2007; van Blerk & Ansell, 2007; Young & Ansell, 2003): “[My uncle] said: ‘you are not my child so I cannot send you to school’” (Foster et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies (6/15) identified stigma as predisposing to maltreatment (Ansell & Young, 2004; Funkquist et al, 2007; Harms et al, 2009, 2010; McGraw & Wameyo, 2005; Snipstad et al, 2005; Wood et al, 2006; Young & Ansell, 2003). Stigma contributed to intra-household discrimination, neglect and emotional abuse (Funkquist et al, 2007; Harms et al, 2009, 2010; McGraw & Wameyo, 2005; Snipstad et al, 2005; Young & Ansell, 2003):

When my father comes home she [my stepmother] tells him that she will give me food on the plate where the dog feeds.

…”
Section: Resultsmentioning
confidence: 99%
“…Recently the literature has started to explore the psychological impact on HIV/AIDS affected children (see for example Cluver et al, 2007;Cluver & Garner, 2007;Harms et al, 2009). …”
Section: Psychosocial Well-beingmentioning
confidence: 99%